Interactions between glycerol, PEG-200 and (NH4)2 SO4 in the stability of heterologous cutinase - Gomes, Daniela S. (2013)
Cutinases (EC 3.1.1.74)are versatile enzymes that have hydrolytic activity on various esters [1]. The spacial structure and the catalytic site of the enzymes can be protected by chemical additives to promove the stability of the activity [2, 3]. The goal of this work was to improve the stability of a recombinant cutinase produced by Escherichia coli.